Findings of preoperative patient risk factors to predict dislocation following total hip arthroplasty - Li, Hao; Xie, Jinwei; Lu, Xiaomin; Li, Shuai; Liao, Weiming (Frontiers in Cell and Developmental Biology, 2025)
BackgroundPrevious studies have identified some risk factors of dislocation after total hip arthroplasty (THA). However, there are many vital preoperative patient risk factors remaining unknown. This study aimed to investigate comprehensively patient risk factors to reduce the dislocation rate after THA.MethodsWe retrospectively reviewed patients who underwent primary THA in our department between January 2016 to December 2020. All readmissions related to postoperative dislocation were recorded, and each patient who dislocated was matched with three patients who did not dislocate according to date of operation, operative time and follow-up time. Patient risk factors were initially analyzed by univariate analyses, and independent risk factors for dislocation were identified by multivariate logistic regression.ResultsA total of 5,133 patients were reviewed and 76 patients were readmitted with postoperative dislocations in follow-up time (1.5%). Age (odds ratio [OR], 1.027; 95% confidence interval [CI], 1.000–1.055; P = 0.049), rheumatoid arthritis (OR, 7.976; 95% CI, 1.419–44.827; P = 0.018), low serum calcium level (OR, 0.009; 95% CI, 0.000–0.211; P = 0.003) and poor education degree (OR, 0.847; 95% CI, 0.770–0.932; P = 0.001) were determined as independent predictors associated with dislocation after THA.ConclusionPatients with older age, rheumatoid arthritis, low serum calcium level, and poor education degree require targeted optimization of preoperative planning and should be performed by appropriate surgical techniques and hip prostheses to prevent dislocation after THA and revision surgeries.